THE DEVELOPMENT OF ICT-ASSISTED EDUCATIONAL MATH GAME “GAMA” WITH CONTEXTUAL TEACHING LEARNING APPROACH - Rafiantika Megahnia Prihandini; Susi Setiawani; Orel Revo Sackhi Usdelivian (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
Educational math game creates a fun learning experience for students. Following this rationale, this research-and-development study aims to elaborate on the process of developing ICT-assisted instructional media named “GAMA”, an educational math game tailored to Contextual Teaching Learning approach. We analyzed the feasibility of the game media to support the instruction on the concept of numbers at the first grade of elementary education. The subjects of this research were the first-grade elementary school students. The study applied the ADDIE development model consisting of five stages with an evaluation at each stage. The research results demonstrated that the game achieved a decent validity score. The practicality test, conducted through questionnaires and observations, documented a practicality score of 90.36%. In addition, the game satisfied the effectiveness test as evaluated through the comparison of students’ learning outcomes based on the N-Gain score of 0.76. This implied a significant difference between students' understanding before and after using educational math games.